The genus Laccobius in China: new species and new records (Coleoptera: Hydrophilidae) - Jia, Fenglong; Gentili, Elio; Fikáček, Martin (Zootaxa, 2013)
The species of the water scavenger beetle genus Laccobius Erichson, 1837 occuring in China are reviewed. Two new species are described: Laccobius (Glyptolaccobius) qinlingensis sp. nov. (Shaanxi) and L. (Cyclolaccobius) hainanensis sp. nov. (Hainan). Five species are recorded for the first time: Laccobius (Dimorpholaccobius) bipunctatus (Fabricius, 1775), L. (D.) striatulus (Fabricius, 1801) and L. (Compsolaccobius) pallidissimus Reitter, 1899 (all from Xinjiang), L. (Microlaccobius) tonkinensis Gentili, 1979 (Shaanxi), and L. (Compsolaccobius) decorus (Gyllenhal, 1827) (Qinghai). Additional faunistic data from China are provided for the following species: L. (Cyclolaccobius) hingstoni Orchymont, 1926, L. (C.) nitidus Gentili, 1984, L. (C.) politus Gentili, 1979, L. (C.) yunnanensis Gentili, 2003, L. (Dimorpholaccobius) simulans Orchymont, 1923, L. (s.str.) binotatus Orchymont, 1934, L. (s.str.) cinereus Motschulsky, 1860, L. (s.str.) colon (Stephens, 1829), L. (s.str.) inopinus Gentili, 1980, L. (s.str.) minutus (Linnaeus, 1758), L. (s.str.) nobilis Gentili, 1979, L. (Microlaccobius) elegans Gentili, 1979, L. (M.) florens Gentili, 1979, L. (M.) formosus Gentili, 1979, L. (M.) hammondi Gentili, 1984, L. (M.) himalayanus Gentili, 1988, and L. (M.) nepalensis Gentili, 1982. An updated checklist of Laccobius species occurring inChina is provided.